Can varying the number of teams in a shift schedule constitute a preventive strategy? - Hans Jeppe Jeppesen; Magnar Kleiven; Henrik Bøggild (Revista de Saúde Pública)
OBJECTIVE: The study examines the implications for shiftworkers of applying different numbers of teams in the organization of shiftwork. METHODS: The participating operators came from five different companies applying continuous shift rotation systems. The companies shared the same product organization and a common corporate culture belonging to the same multinational company. Each company had a shift system consisting of four, five or six teams, with the proportion of shifts outside day work decreasing as the number of teams increased. Questionnaire and documentary data were used as data sources. RESULTS: Operators in systems with additional teams had more daywork but also more irregular working hours due to both overtime and schedule changes. Operators using six teams used fewer social compensation strategies. Operators in four teams were most satisfied with their work hours. Satisfaction with the time available for various social activities outside work varied inconsistently between the groups. CONCLUSIONS: In rotating systems the application of more teams reduces the number of shifts outside day work. This apparent improvement for shiftworkers was counteracted by a concomitant irregularity produced by greater organizational requirements for flexibility. The balance of this interaction was found to have a critical impact on employees.